11.9k views
0 votes
Write the expression using exponents. (-5)(-5)(-5)(-5)

User Suela
by
5.3k points

2 Answers

1 vote

Answer:

(-5)^4

Explanation:

^4 is the exponent

You must have the parentheses.

User Mike Griffith
by
5.1k points
6 votes

Answer:

(-5)(-5)(-5)(-5) = (-5)⁴

Explanation:

First Let’s take some examples for better understanding :

Example 1 :

a² = a × a

a³ = a × a × a

a¹⁰ = a × a × a × a × a × a × a × a × a × a (a is multiplied by itself 10 times)

Example 2 :

3 × 3 = 3²

3 × 3 × 3 × 3 = 3⁴

………………………

According to what we have learned :

In the example: (-5)(-5)(-5)(-5) the base number -5 is repeated 4 times.

Then

(-5)(-5)(-5)(-5) = (-5)⁴

User Jhashane
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.